The leisure activity settings and experiences of youth with severe disabilities. (August 2014) - King, Gillian; Batorowicz, Beata; Rigby, Patty; Pinto, Madhu; Thompson, Laura; Goh, Freda
Abstract Objective: The objective was to describe the leisure activity settings of youth with severe disabilities, the environmental qualities of these settings, and youths' experiences. Methods: Fifteen youth using augmentative and alternative communication and 11 with complex continuing care needs took part in 54 leisure activity settings of their own choosing. Following their participation, they completed the Self-Reported Experiences of Activity Settings questionnaire and trained observers completed the Measure of Environmental Qualities of Activity Settings. Results: Youths' selected activity settings provided relatively high opportunities for choice, interaction with adults, and social activities, and youth experienced relatively high levels of psychological engagement, social belonging, and control and choice. Youth primarily took part in activity settings that provided opportunities for competency/relatedness and involved others. Conclusion: Implications for future research and clinical practice include the importance of valuing passive recreational activities for the opportunities for challenge, choice, and social interaction they provide.